Viral Reservoir in Early-Treated Human Immunodeficiency Virus-Infected Children and Markers for Sustained Viral Suppression. (19th February 2021) - Ajibola, Gbolahan; Garcia-Broncano, Pilar; Maswabi, Kenneth; Bennett, Kara; Hughes, Michael D; Moyo, Sikhulile; Mohammed, Terrence; Jean-Philippe, Patrick; Sakoi, Maureen; Batlang, Oganne; Lockman, Shahin; Makhema, Joseph; et al.
Abstract: Background: The impact of very early infant treatment on human immunodeficiency virus (HIV) reservoir, and markers for treatment success, require study. Methods: The Early Infant Treatment Study (EIT) enrolled 40 children living with HIV started on antiretroviral treatment (ART) at <7 days of age, with 23 who had started treatment between 30–365 days to serve as controls. Quantitative HIV DNA was evaluated every 1–3 months in peripheral blood mononuclear cells. 84-week repeat qualitative whole blood DNA polymerase chain reaction and dual enzyme immunosorbent assay were performed. Results: Median quantitative cell-associated DNA after at least 84 weeks was significantly lower among the first 27 EIT children tested than among 10 controls (40.8 vs 981.4 copies/million cells; P  < .001) and correlated with pre-ART DNA. Median DNA after 84 weeks did not differ significantly by negative or positive serostatus at 84 weeks ( P  = .94), and appeared unaffected by periods of unsuppressed plasma RNA from 24–84 weeks ( P  = .70). However, negative 84-week serostatus was 67% predictive for sustained RNA suppression, and positive serostatus was 100% predictive for viremia. Loss of qualitative DNA positivity at 84 weeks was 73% predictive for sustained suppression, and persistent positivity was 77% predictive for viremia. Conclusions: Lower viral reservoir was associated with starting ART at <1 week. Negative serostatus and qualitative DNA were useful markers of sustained viral suppression from 24–84 weeks. Abstract : Infants starting antiretroviral therapy at <1 week had lower 84-week proviral reservoir than controls. Serostatus and qualitative DNA were useful markers for rebound, but transient viremia between 24–84 weeks had no apparent impact on the viral reservoir in peripheral blood mononuclear cells.